The Interaction of Bacteria with Engineered Nanostructured Polymeric Materials: A Review - Ilaria Armentano; Carla Renata Arciola; Elena Fortunati; Davide Ferrari; Samantha Mattioli; Concetta Floriana Amoroso; Jessica Rizzo; Jose M. Kenny; Marcello Imbriani; Livia Visai (The Scientific World Journal)
Bacterial infections are a leading cause of morbidity and mortality worldwide. In spite of great advances in biomaterials research and development, a significant proportion of medical devices undergo bacterial colonization and become the target of an implant-related infection. We present a review of the two major classes of antibacterial nanostructured materials: polymeric nanocomposites and surface-engineered materials. The paper describes antibacterial effects due to the induced material properties, along with the principles of bacterial adhesion and the biofilm formation process. Methods for antimicrobial modifications of polymers using a nanocomposite approach as well as surface modification procedures are surveyed and discussed, followed by a concise examination of techniques used in estimating bacteria/material interactions. Finally, we present an outline of future sceneries and perspectives on antibacterial applications of nanostructured materials to resist or counteract implant infections.